Radiotherapy plus androgen deprivation therapy for prostate‐specific antigen persistence in lymph node–positive prostate cancer. Issue 7 (17th May 2022) - Shiota, Masaki; Takamatsu, Dai; Kimura, Takahiro; Tashiro, Kojiro; Matsui, Yoshiyuki; Tomida, Ryotaro; Saito, Ryoichi; Tsutsumi, Masakazu; Yokomizo, Akira; Yamamoto, Yoshiyuki; Edamura, Kohei; Miyake, Makito; et al.
Abstract: The treatment for lymph node involvement (LNI) after radical prostatectomy (RP) has not been established. This study aimed to reveal the outcomes of various management strategies among patients with LNI after RP. Retrospectively, 561 patients with LNI after pelvic lymph node dissection (PLND) with RP treated between 2006 and 2019 at 33 institutions participating in the Japanese Urological Oncology Group were investigated. Metastasis‐free survival (MFS) was the primary outcome. Patients were stratified by prostate‐specific antigen (PSA) persistence after RP. Cox regression models were used to analyze the relationships between clinicopathological characteristics and survival. Survival analyses were conducted using the Kaplan‐Meier method and log‐rank test with or without propensity score matching. Prognoses, including MFS and overall survival, were prominently inferior among patients with persistent PSA compared with those without persistent PSA. In multivariate analysis, androgen deprivation therapy (ADT) plus radiotherapy (RT) was associated with better MFS than ADT alone among patients with persistent PSA (hazard ratio = 0.37; 95% confidence interval = 0.15‐0.93; p = 0.034). Similarly, MFS and overall survival were significantly better for ADT plus RT than for ADT alone among patients with persistent PSA after propensity score matching. This study indicated that PSA persistence in LNI prostate cancer increased the risk of poor prognoses, and intensive treatment featuring the addition of RT to ADT might improve survival. Abstract : The treatment for lymph node involvement (LNI) after radical prostatectomy (RP) among patients with persistent prostate‐specific antigen (PSA) after RP has not been established. Here, the outcomes of various management strategies among patients with LNI after RP were investigated. This study indicated that PSA persistence in LNI prostate cancer increased the risk of poor prognoses, and intensive treatment featuring the addition of RT to androgen deprivation therapy (ADT) might improve survival.